Capturing T Lymphocytes’ Dynamic Interactions With Human Neural Cells Using Time-Lapse Microscopy - Lemaître, Florent; Carmena Moratalla, Ana; Farzam-kia, Negar; Carpentier Solorio, Yves; Tastet, Olivier; Cleret-Buhot, Aurélie; Guimond, Jean Victor; Haddad, Elie; Arbour, Nathalie (Frontiers in Immunology, 2021)
To fully perform their functions, T lymphocytes migrate within organs’ parenchyma and interact with local cells. Infiltration of T lymphocytes within the central nervous system (CNS) is associated with numerous neurodegenerative disorders. Nevertheless, how these immune cells communicate and respond to neural cells remains unresolved. To investigate the behavior of T lymphocytes that reach the CNS, we have established an in vitro co-culture model and analyzed the spatiotemporal interactions between human activated CD8+ T lymphocytes and primary human astrocytes and neurons using time-lapse microscopy. By combining multiple variables extracted from individual CD8+ T cell tracking, we show that CD8+ T lymphocytes adopt a more motile and exploratory behavior upon interacting with astrocytes than with neurons. Pretreatment of astrocytes or neurons with IL-1β to mimic in vivo inflammation significantly increases CD8+ T lymphocyte motility. Using visual interpretation and analysis of numerical variables extracted from CD8+ T cell tracking, we identified four distinct CD8+ T lymphocyte behaviors: scanning, dancing, poking and round. IL-1β-pretreatment significantly increases the proportion of scanning CD8+ T lymphocytes, which are characterized by active exploration, and reduces the proportion of round CD8+ T lymphocytes, which are less active. Blocking MHC class I on astrocytes significantly diminishes the proportion of poking CD8+ T lymphocytes, which exhibit synapse-like interactions. Lastly, our co-culture time-lapse model is easily adaptable and sufficiently sensitive and powerful to characterize and quantify spatiotemporal interactions between human T lymphocytes and primary human cells in different conditions while preserving viability of fragile cells such as neurons and astrocytes.